Density estimation communication systems - Wang, Peng (2008)
Density estimation refers to a family of techniques that attempt to model the statistics (e.g. the probability density function) of a signal based on a sequence of observations. While parametric density estimation has been widely used in communications, non- and semi-parametric density estimation has received much less attention. The objective of this study is to investigate the possibility of using non- and semi-parametric density estimation techniques to solve the problems that cannot be easily handled with parametric approaches. In particular, two problems have been investigated: the estimation of the error rate and the mitigation of the inter-symbol interference.